2016
DOI: 10.15376/biores.11.1.2655-2664
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Dynamic Viscoelasticity of Bamboo Kraft Black Liquor

Abstract: The dynamic viscoelasticity of bamboo kraft pulping black liquor under various temperatures (ranging from 50 to 80 °C) and solids concentrations (60 to 80 wt.%) was studied. Rotational rheometer analysis data indicated that the viscoelastic motion law with a high solids concentration in black liquor was in accordance with the Kelvin model, and black liquor with a medium concentration conformed to the Maxwell model. As a result, the temperature and solids concentration greatly influenced the dynamic viscoelasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The authors considered that the rheological properties of thick BL can influence the atomization and combustion of BL, so the dynamic viscoelasticity and rheological properties of thick bamboo kraft pulping BL has been studied (Xu et al 2016a;Yue et al , 2018. The results showed that it was the primary task to realize the high concentration combustion technology of non-wood pulping BL to solve the problem of high viscosity and dilatability of thick bamboo kraft pulping BL (Xu et al 2016a;. In this study, sodium aluminate and basic magnesium carbonate were used as desilication agents, and the desilication effect was studied deeply for both the aluminum salt and Mg-Al compound desilication agents.…”
Section: Introductionmentioning
confidence: 99%
“…The authors considered that the rheological properties of thick BL can influence the atomization and combustion of BL, so the dynamic viscoelasticity and rheological properties of thick bamboo kraft pulping BL has been studied (Xu et al 2016a;Yue et al , 2018. The results showed that it was the primary task to realize the high concentration combustion technology of non-wood pulping BL to solve the problem of high viscosity and dilatability of thick bamboo kraft pulping BL (Xu et al 2016a;. In this study, sodium aluminate and basic magnesium carbonate were used as desilication agents, and the desilication effect was studied deeply for both the aluminum salt and Mg-Al compound desilication agents.…”
Section: Introductionmentioning
confidence: 99%
“…The silicide in raw materials reacts with alkali to produce Na2SiO3 dissolved into the black liquor, which will cause a series of trouble, named "silicon interference" problems. One of the problems is that the viscosity of BKBL will increase rapidly with the increase in silicon content, which brings problems to black liquor pumping and atomization and then has an influence on the evaporation and combustion efficiency (Zaman and Fricke 1996;Liu et al 2013;Xu et al 2016aXu et al , 2016b. The black liquor forms a liquid film when hitting the splash-plate nozzle at a higher speed by accelerating in the barrel of spray gun, and this process is defined as an atomization (Barreras et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of bamboo kraft paper is superior to that of straw pulp paper. Hence, bamboo is considered a favorable papermaking material (Xu et al 2016a).…”
Section: Introductionmentioning
confidence: 99%